2015
DOI: 10.1093/jxb/erv103
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis reveals dynamic changes in expression of microRNAs during vascular cambium development in Chinese fir, Cunninghamia lanceolata

Abstract: MicroRNAs (miRNAs) are small noncoding regulatory RNAs that play key roles in the process of plant development. To date, extensive studies of miRNAs have been performed in a few model plants, but few efforts have focused on small RNAs (sRNAs) in conifers because of the lack of reference sequences for their enormous genomes. In this study, Solexa sequencing of three sRNA libraries obtained from dormant, reactivating, and active vascular cambium in Chinese fir (Cunninghamia lanceolata) using tangential cryosectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 42 publications
2
40
2
Order By: Relevance
“…Another common HKG, EF1a , was validated as one of the best choices for Brachiaria brizantha [54]. In previous studies, scientists have applied and identified HKGs as internal control genes in different tissues of Chinese fir, including leaves, shoot apical meristems, stems, barks, xylems and vascular cambiums [4,5,55,56]. However, identification of HKGs in Chinese fir seedlings upon different abiotic stresses has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another common HKG, EF1a , was validated as one of the best choices for Brachiaria brizantha [54]. In previous studies, scientists have applied and identified HKGs as internal control genes in different tissues of Chinese fir, including leaves, shoot apical meristems, stems, barks, xylems and vascular cambiums [4,5,55,56]. However, identification of HKGs in Chinese fir seedlings upon different abiotic stresses has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese fir is a fast-growing conifer that belongs to family Cupressaceae, and is a commercially important tree of the lumber, pulp, and paper industry. Biological studies have recently revealed the molecular mechanism underlying the control of the developmental processes and physiological responses of the Chinese fir [4,5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, 30 m sections were isolated by tangential cryosectioning at −24 • C with a Leica CM1850 Cryostat (Leica Microsystems Nussloch GmbH, Germany) equipped with a steel knife. Transverse sections taken from both ends of the specimen and stained with aniline blue were used to locate the position of tangential sections, as described previously (Qiu et al, 2015).…”
Section: Plant Materialsmentioning
confidence: 99%
“…During the past decades, millions of C. lanceolat trees have been planted and more areas are being re-planted as second or later rotation (Zhang et al, 2004). Based on our previous investigations in C. lanceolata (Wan et al, 2012;Qiu et al, 2013;Qiu et al, 2015), we further examined the transcriptome profile of cambial meristem at these three developmental stages, combined with the morphological analysis. To the best of our knowledge, this study is the first to characterize the transcriptome dynamics of coniferous trees during the transition from juvenile to mature stages, which then provides new insights into the molecular mechanisms underlying vascular cambium development and wood production.…”
Section: Introductionmentioning
confidence: 99%